Sensitized [2 + 2] intramolecular photocycloaddition of unsaturated enones using UV LEDs in a continuous flow reactor: kinetic and preparative aspects. Issue 5 (13th February 2019) - El Achi, Nassim; Gelat, Fabien; Cheval, Nicolas P.; Mazzah, Ahmed; Bakkour, Youssef; Penhoat, Maël; Chausset-Boissarie, Laëtitia; Rolando, Christian
Abstract : A photocatalysed cycloaddition by benzophenone derivatives under flow and UVA LED irradiation is described. Abstract : A catalytically sensitized intramolecular [2 + 2] photocycloaddition reaction of 3-alkenyloxy-2-cycloalkenones onto cyclobutanes was studied using a flow microreactor irradiated by high power UV-A LEDs. During the course of the study we also identified an ionic liquid photosensitizer that facilitates the purification of the photocycloaddition product. Good to excellent yields were obtained in flow for a variety of substrates by applying significantly shorter residence times than those needed in a conventional batch reactor. The flow device enabled the determination of highly accurate kinetic data which supported a second order reaction rate in the substrate and photocatalyst for the [2 + 2] photocycloaddition reaction and a first order in the photocatalyst for the pinacolisation of the sensitizer. Furthermore, the kinetic model and flow chemistry data enabled us to obtain excellent fits for both cyclobutane and pinacol even at almost full conversions.